Upaya Pengenalan Masalah Kesehatan Pada Keluarga ny. S Khususnya an. Z Dengan Status Gizi Kurang Di Kabupaten Sukoharjo - Agustiawan, Rozi, H.M. Abi Muhlisin, SKM., M.Kep (2016)
Nutritional deficiency worldwide is one cause of death in children under 5 years of age due to a lack of nutrients, energy and protein which is the main energy source in humans in this case children under the age of 5 years. Methods : Essay writer stacking using descriptive method with case study approach that the scientific method is to collect data, analyze the data and draw conclusions data. Results : From the results of nursing care found that output in Mrs. S lack of knowledge about the health problems that occur in Child. Z causing An. Z deficiency in nutrition less than -3.3 curve by WHO in 2006 so that in this case the author as nurses provide nursing care in the form of health education regarding balanced nutrition in a child's age Child. Z Conclusion : The family is the center of health care in total, because if one of the family members have health problems it will affect the system of the family members, family nursing care done by the family nursing approach.